Exploration of the Main Models and Optimization Paths for the Market-Oriented Operation of Urban Parks - Yanting LI; Qiaowan YANG (Fengjing Yuanlin)
ObjectiveAgainst the backdrop of ecological civilization construction and driven by the people’s demand for a better life, urban parks, as representatives of green spaces, are no longer merely for “scenic appreciation”. Instead, they have gradually evolved from traditional places of leisure into urban vitality centers that integrate multiple functions, including ecological conservation, public services, and economic operation. However, over the past few decades, parks have mainly been constructed and managed by the government, heavily relying on fiscal input. They have been in a state of focusing on construction while neglecting management and operation, resulting in a single type of public product. In recent years, with the tightening of policy and fiscal funds, the funding gap for park management and maintenance has been continuously expanding. Many cities have been trying to adopt market-oriented approaches by introducing diverse investment and operation entities. However, under the current management system, market-oriented operation models face many difficulties. The policy details have not yet been issued, market investment confidence is insufficient, and the market is still in its infancy, making it very difficult to implement the aforesaid operation models, consequently resulting in insufficient effective supply of public services. Under this background, analyzing the existing operation models and conducting research on innovative paths is of great reference significance for exploring the improvement and efficiency enhancement of urban parks.MethodsAt present, research on park operation in China is still in its infancy, with few results. Some cities have some sporadic practices and experiences. Based on the above background, this research has preliminarily sorted out the park operation models currently implemented in China. The research includes not only the operation and management models of park green spaces themselves but also the operation cases of urban areas involving park green spaces. These include the model of integrating park property management and commercial operation as a whole package, the model of sharing risks and profits between the government and enterprises, the model of innovative mixed land use in cultural and tourist attractions, and the model of overall operation of urban areas led by urban operators. The profit models, incentive and constraint conditions, and market feedback of different stakeholders in these four models are compared. The institutional bottlenecks and implementation difficulties of the existing operation models are systematically analyzed. The current dilemma of balancing the public welfare and commercial aspects of parks as a public product is put forward together with the difficulties involved in park management, such as the complexity of cross-departmental coordination, and the lack of detailed policy basis and effective profit distribution system.ResultsBy constructing an “all-in-one map” of spatio-temporal park assets to achieve three-dimensional quantification of spatial assets, an inventory of the land, buildings, and facilities within parks is conducted, park plan is spatially classified, and in combination with the demand for mixed land use featuring the combination of dominance by public welfare and flexible compatibility”, park space is divided into core conservation areas, compatible utilization areas, and market revitalization areas. At the same time, the method of layered ownership confirmation can be achieved by superimposing underground space, multi-story properties, skywalks, etc. Attempts are made to establish property ownership division rules and rent assessment for the same space at different elevations, and to manage the three-dimensional space more precisely. In addition, time-sharing land supply methods for the same site at different times are considered, and cyclical business activities are carried out. The public welfare and openness are emphasized during non-business hours, while the commercial value of space is explored during business hours, ultimately forming the baseline of parks’ spatial assets. A light-asset operation product matrix is customized according to the characteristics of parks to release the traffic and cultural potential of parks. For large theme parks with specific amusement products, the physical space limitations can be broken. Immersive experiences and new consumption models can be created using AR/VR technology. Digital collectibles can be developed, and online concerts and cultural exhibitions can be held. Linkages with game, film, and other IPs can be established to create cross-border experiences and diverse commercial ecosystems for parks. With cultural and digital assets as the core to activate low-cost and high-efficiency sustainable operations, diversified financing channels are explored. Based on the “all-in-one map” of spatio-temporal park assets, the future income rights of park business assets are packaged into standardized financial products to attract medium and long-term capital investment. The data assets, cultural assets, and IP copyrights of park activities can be traded on digital platforms to realize the value of virtual assets. The greening area and carbon sequestration capacity of parks can be monetized through the carbon trading market. By transforming static spatial assets into financial targets with stable cash flow, the government debt pressure is reduced. A closed loop of “physical space operation − digital asset appreciation − financial tools feedback” is constructed, forming a sustainable development paradigm for the market-oriented operation of public welfare assets.ConclusionWhen cities enter the era of refined operation, park operation is no longer a simple proposition based on public green spaces, but a complex system project involving public finance, spatial economy, and social governance. At present, many cities in China have been actively exploring and innovating in the field of market-oriented park operation, but they have also faced many contradictions. The public welfare of parks as a public product restricts the release of commercial potential, policy barriers increase transaction costs, and imbalanced profit distribution intensifies the game between the government and enterprises. How to respond to these difficulties and explore solutions is not only related to the improvement of urban governance efficiency but also to the deepening of the practice of the “people’s city” concept. Only through systematic design can the problem be solved. On this basis, through innovation in institutional design and market guidance, implementation paths are proposed to explore how to resolve the contradictions between the public and commercial attributes of parks and balance the short-term interests of parks with long-term ecological benefits, providing practical references for park authorities and operation implementation units.